GCMS profiling of bioactive phytocompounds from Curculigo orchiodes Gaertn. root extract and evaluation of antioxidant, and antidiabetic activities: A computational drug development approach - Mahmud, Imran; Saifullah, Md. Khalid; Morshed, Md. Niaj; Hossain, Md. Arju; Shahria, Naznin; Barman, Apurba Kumar; Ahmed, Famim; Islam, Md. Jakaria; Khan, Toufiq Ejaj; Biswas, Nripendra Nath (PLOS ONE, 2025)
Curculigo orchioides (C. orchioides), a traditionally valued medicinal plant, has been utilized for centuries in the management of various ailments, but its full spectrum of therapeutical potentials remains underexplored. This study aimed to perform GC-MS profiling of bioactive phytochemicals as well as to evaluate the antioxidant and anti-diabetic properties of the ethanolic root extract of C. orchioides (ERCO) through an integrative approach combining in vitro, in vivo, and in silico methods. Phytochemical screening confirmed the presence of some major bioactive phytochemical groups including alkaloids, flavonoids, tannins, saponins, and steroids which are well-known for their pharmacological relevance. Antioxidant activity was demonstrated through high levels of total phenolic content (TPC), total flavonoid content (TFC), total tannin content (TTC) determined as 44.055 mg GAE/gm, 0.6768 mg QE/gm, and 103.375 mg TAE/gm of dry weight extract, respectively, along with notable ferric reducing antioxidant power (FRAP). Anti-diabetic potential was supported by significant in vitro inhibition of pancreatic α-amylase and α-glucosidase enzymes, with IC50 values of 84.17 μg/mL and 36.33 μg/mL, respectively. In vivo studies in alloxan-induced diabetic mice further validated the extract’s substantial blood glucose-reduction abilities (47.28% and 52.11% at the dose of 100 mg/kg and 200 mg/kg body-weight, respectively), indicating the potential for blood sugar regulation. GC-MS profiling confirmed the presence of 23 major phytochemicals, which were subjected to molecular docking studies against human glutathione peroxidase, peroxiredoxin 5, Catalase, sulfonylurea receptor 1 (SUR1), α-amylase, and α-glucosidase. Among them, 2-epoxy-3,4-dihydroxycyclohexano[a]pyrene (CID: 41322) emerged as a lead compound, exhibiting strong binding affinities for both α-amylase (−9.1 kcal/mol) and α-glucosidase (−8.8 kcal/mol). ADMET predictions and stable molecular dynamics simulation outcomes further underscored its drug-likeness. Collectively, these findings position ERCO as a promising source of natural antioxidants and anti-diabetic agents, while identifying 2-epoxy-3,4-dihydroxycyclohexano[a]pyrene as a potential therapeutic lead. This investigation provides a foundation for future drug development, and, further experimental validations, isolation of active compounds, and subsequent clinical studies are required to validate its safety and efficacy.